Patient-reported outcome measures to assess mental and physical health status, functionality, and quality of life in patients with major depression or schizophrenia - Luis San; Belen Arranz; Carlota Romans; Berta García; Marta Coromina; Sonia Ortiz; Miriam Vilaplana; Víctor Soto; Ruth Villaescusa; Joan Alvaros (Journal of Patient-Reported Outcomes)
Abstract Background Patient-reported outcomes measures (PROMs) are standardized self-administered tools that assess the patient’s opinion on the level of health, quality of life, and disability among other aspects. The objective of this study was to gather information on physical and mental health in patients with major mental illness using PROMs. Methods This was an observational, naturalistic, prospective study carried out in adult stabilized outpatients attended at nine Adult Mental Health Centers in Barcelona, Spain. All participants had a confirmed diagnosis of major depression disorder or schizophrenia (DSM-5) and were currently on drug treatment. Participants (n = 508) self-completed a baseline questionnaire for clinical data and PROMs scales (PHQ-19, SF-12, and WHODAS 2.0) at baseline and 9 months thereafter (n = 482). Results Mean (SD) age was 50.9 (13.2) years, and 83% of patients lived with their families. Although 93.9% of patients recognized having a mental illness, 15.7% did not know their diagnosis. When asked if they considered that during the last year their treatment had offered some type of improvement, 83.9% answered affirmatively. Patients reported that their degree of adherence to treatment was high (77%) and most of them (80%) believed the medication had a beneficial effect. Depressed patients showed both at baseline and at follow up significantly more depressive symptoms than the group with schizophrenia. In the schizophrenia group, a statistically significant improvement in depressive symptoms was noted at 9 months follow-up. We did not find significant differences within or between groups in quality of life (SF-12 scores) obtained at baseline and after 9 months of follow-up Both at baseline and at follow-up, patients with depression reported a significantly higher degree of disability (WHODAS scores) than those with schizophrenia. Conclusions PROMs can be used in real-world conditions to assess severity of disease, quality of life, and disability in major depression and schizophrenia. The present results are relevant for both patients and clinicians.